Real world experience on the effectiveness and safety of pirfenidone in patients with idiopathic pulmonary fibrosis in Taiwan - Chang, Cheng-Yu; Wei, Yu-Feng; Chen, Chung-Yu; Lai, Yi-Chun; Hu, Po-Wei; Hung, Jui-Chi; Chu, Chi-Hsiang; Chuang, Hsin-Tzu; Chang, Shih-Chieh (Frontiers in Medicine, 2023)
Introduction Randomized controlled trials have demonstrated a reduction in the decline of lung function and a reduced risk of acute exacerbation in patients with idiopathic pulmonary fibrosis treated with the antifibrotic prifenidone. The present study aimed to investigate the real-world effectiveness and safety profile of pirfenidone treatment for patients with IPF in Taiwan. Methods Between January 1, 2019 and December 31, 2020, we enrolled 50 patients who were newly diagnosed with IPF and had at least 12 months follow-up period after pirfenidone administration. Result The primary outcome of pharmacologic effect showed that the mean differences in the absolute values of forced vital capacity from baseline were 0.2 liter (n = 36), 0.13 liter (n = 32), 0.04 liter (n = 26), and − 0.004 liter (n = 26) after 3, 6, 9, and 12 months of administration, respectively. A slight improvement in quality of life, including scores of chronic obstructive pulmonary disease assessment test and St. George’s respiratory questionnaire scores. The most common adverse effects were gastrointestinal upset and dermatological problems. No new safety concerns were observed in the present study. Conclusion Our real-world study describe for the first time in Taiwan, the use of pirfenidone over a 12 months period. This drug preserves the lung function and improves quality of life with tolerable side effects.